The Influence of Brand Personality, Supporter Trust, Supporter Satisfaction Against Supporter Commitment (Empirical Study: Fans of The Indonesian National Football Team) - Riski Gazali; Kandi Sofia Senastri Dahlan (Journal of World Science, 2024)
Sport, particularly football, is a field with a vast fan base, where the loyalty and commitment of fans play a crucial role in a team's success. A football team functions much like a brand, and similar to any product or service, fans have specific criteria that drive their support and commitment to their favorite team. This research aims to analyze the factors that shape fan commitment, enabling football teams to better cater to their supporters' expectations. The study specifically examines variables such as Brand Personality, Supporter Commitment, Supporter Trust, and Supporter Satisfaction. The primary objective is to identify the key factors that are essential for building a strong commitment among football fans towards their beloved teams. The research adopts a quantitative approach, targeting a sample size of at least 100 participants. Data was collected through online questionnaires, and the analysis was conducted using Structural Equation Modeling (SEM) via SmartPLS 3.0, assessing both the outer and inner models. The findings reveal that the Brand Personality of the Indonesian National Football Team has a positive and significant impact on Supporter Trust, Supporter Commitment, and Supporter Satisfaction. These results imply that by understanding and enhancing the brand personality, football teams can effectively foster greater trust, commitment, and satisfaction among their fans, leading to a stronger and more loyal supporter base.